“It’s Not Only Our Task”: Administrative Barriers of Enabling Urban Gardening in Tampere, Finland - Willman, Krista (ACME, 2023)
An ongoing academic debate shows that urban community gardening (CG) has diverse governance models with differing roles of city administration and citizens. This article uses an empirical case study conducted in the city of Tampere, Finland, to explore what I call the “operational space” of urban CG seen from the viewpoint of city officials. Two rounds of interviews were conducted with eight city officials, and a discourse analysis was applied for the data. As an analytic term developed in this article, the operational space emerges by administrative policies and practices that enable or constrain urban gardening under two general trends of urban governance: institutional ambiguity and neoliberal urban development. In this case, the operational space was rather rigid and narrow. The five main discourses on benefit, control of space, scarcity, unclarity, and newness referred to a clear aim to enable urban gardening. However, the discourses were restricted to strategic, limited, and instrumental levels, as the political-strategic aims of enabling urban gardening contradicted the administrative practices. The results show that cautiousness and unclarity in the administrative-political culture tend to lead to institutional ambiguity. In conclusion, operational space analysis is helpful to uncover the problems and possibilities between CG and city administration.